2018
DOI: 10.3390/ijerph15092000
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in Childhood Vaccination Coverage in Zhejiang, Province: Evidence from a Decomposition Analysis on Two-Round Surveys

Abstract: Objective: The objectives of this study were to determine the degree and risk factors of the inequity in the childhood coverage of full primary immunization (FPI) in Zhejiang province. Method: We used data from two rounds of vaccination coverage surveys among children aged 24–35 months conducted in 2014 and 2017, respectively. The household income per month was used as an index of socioeconomic status for the inequality analysis. The concentration index (CI) was used to quantify the degree of inequality, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 36 publications
(38 reference statements)
0
17
0
Order By: Relevance
“…Although Zhejiang province has an effective and efficient immunization program, some perplexing variations within the province still exist. Zhejiang province has attained and maintained high coverage (>90% for individual vaccine doses) for almost all the individual antigens in the national vaccination schedule as per administrative reports [6,7], but two rounds of provincially representative surveys (2011 and 2013) have found the surprising gaps in coverage between rural and urban areas to the advantage of rural areas [8]. In Zhejiang province, vaccination services are delivered through fixed clinic sessions conducted at community health centers and all vaccines included in EPI are provided free of charge.…”
Section: Introductionmentioning
confidence: 99%
“…Although Zhejiang province has an effective and efficient immunization program, some perplexing variations within the province still exist. Zhejiang province has attained and maintained high coverage (>90% for individual vaccine doses) for almost all the individual antigens in the national vaccination schedule as per administrative reports [6,7], but two rounds of provincially representative surveys (2011 and 2013) have found the surprising gaps in coverage between rural and urban areas to the advantage of rural areas [8]. In Zhejiang province, vaccination services are delivered through fixed clinic sessions conducted at community health centers and all vaccines included in EPI are provided free of charge.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the substantial variation between countries. In China, the Gambia, Nigeria, and Zambia, for all years of data and included studies, there is a significant relative benefit to being vaccinated given living in a rural area compared to urban settings [49, 97, 46, 48, 50, 80, 92], whereas in Ethiopia, India, Kenya, Myanmar, Pakistan, and Vietnam, the opposite relationship is seen [55, 56, 62, 96, 76, 75, 94, 82, 93]. Similarly, Ameyaw et al and Muche Fenta et al, who examined multiple countries in Africa, found significant relative risks to being vaccinated given residing in rural settings compared to urban areas [19, 24].…”
Section: Resultsmentioning
confidence: 99%
“…For the poor and those who live in remote areas (or areas that are geographically difficult to access), the cost of getting immunized is higher (Hodge et al, 2014). Although basic immunization services are funded by the government (free), the cost of going to a health facility and the opportunity cost to bring a child to a health facility is borne by the household (Bhuiya et al, 1995;Herliana & Douiri, 2017;Hu et al, 2018;Maharani & Tampubolon, 2015). In areas where the number of health facilities is very limited and geographical conditions are difficult, higher costs, both time and actual transportation cost, to visit health facilities hinder many households get their children immunized.…”
Section: Discussionmentioning
confidence: 99%